2007
DOI: 10.1044/1092-4388(2007/053)
|View full text |Cite
|
Sign up to set email alerts
|

Lexical Aspect and the Use of Verb Morphology by Children With Specific Language Impairment

Abstract: Difficulties with tense-related morphology may be compounded in children with SLI if they fail to make use of associations between the lexical aspect of verb predicates and the grammatical function of the accompanying inflections. The authors argue that the advantages of using these associations as a starting point in acquisition may be especially important in the case of -ed. Additional studies of children with SLI are clearly needed, including those that employ longitudinal, naturalistic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 30 publications
2
42
1
2
Order By: Relevance
“…All of the children had been participants in studies conducted by the Child Language Laboratory at Purdue University. These studies involved experimental tasks that focused on the children’s grammatical, lexical, nonword repetition, or attention skills (Deevy, Wisman Weil, Leonard, & Goffman, 2010; Finneran, Francis, & Leonard, 2009; Leonard, Deevy et al, 2007; Leonard, Deevy, Wong, Stokes, & Fletcher, 2007). The spontaneous speech samples analyzed in this study were collected prior to administration of the experimental tasks to document the children’s mean length of utterance and determine whether their developmental level was appropriate for participation in the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…All of the children had been participants in studies conducted by the Child Language Laboratory at Purdue University. These studies involved experimental tasks that focused on the children’s grammatical, lexical, nonword repetition, or attention skills (Deevy, Wisman Weil, Leonard, & Goffman, 2010; Finneran, Francis, & Leonard, 2009; Leonard, Deevy et al, 2007; Leonard, Deevy, Wong, Stokes, & Fletcher, 2007). The spontaneous speech samples analyzed in this study were collected prior to administration of the experimental tasks to document the children’s mean length of utterance and determine whether their developmental level was appropriate for participation in the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Initial studies of children with LI were motivated by models of LI and related these to deficits in the acquisition of language knowledge (Johnston and Kamhi 1984). More recently, studies have focused on a range of domains including pragmatics and/or social cognition (Rapin and Allen 1983, Johnston 1988, Leslie and Frith 1988, lexical semantics (Schwartz and Leonard 1985), and morphosyntax (Curtiss and Tallal 1991, Gopnik and Crago 1991, Leonard 1992. Some of these studies have shown that in younger children the performance of language in agematched controls is similar to that of the children with LI, suggesting that the language-learning system is essentially intact in LI and that delay rather than deviancy best characterizes LI in the early years.…”
mentioning
confidence: 99%
“…Phonological working memory allows one to temporarily store verbal information so that it can be cognitively manipulated for language processing (Adams & Gathercole, 1995;Gathercole & Baddeley, 1993). However, it may also function to support language development (Leonard et al, 2007). For if, as suggested by Leonard et al, a child is unable to retain phonological information in his working memory for a sufficient period of time, then he may have difficulty forming the word's phonological representation.…”
mentioning
confidence: 99%